A review on benchmarking of supply chain performance measures - Wong, Wai Peng (Emerald Group Publishing Ltd., 2008)

(untitled)
Purpose - The purpose of this paper is to redress the imbalances in the past literature of supply chain benchmarking and enhance data envelopment analysis (DEA) modeling approach in supply chain benchmarking. Design/methodology/approach - The paper is sorted into sections: benchmarking, definitions, concepts and literature survey, supply chain benchmarking, problems in supply chain benchmarking, existing tools used in benchmarking, problems in existing tools and motivation of using DEA as a supply chain benchmarking tool. A range of recently published (1995-2004) works is referred and aims to provide insights into possible new research focus in supply chain benchmarking. Findings - Provides information about new trends in supply chain benchmarking and what are the existing problems. Recognizes the lack of mathematical modeling tool in addressing this issue. Research limitations/implications - Supply chain benchmarking is gearing towards a holistic approach. DEA is deemed to be an appropriate benchmarking tool with modifications in existing model. Practical implications - Provide insights to managers on the use of DEA in decision making at strategic level. Originality/value - This paper fulfils an identified information/resources need and offers insights to the future research focus in supply chain benchmarking.